Social-economic burden of severe atopic dermatitis in the Russian Federation - I. S. Krysanov; V. S. Krysanova; O. I. Karpov; V. Yu. Ermakova (Izdatelstvo OKI, 2020)
Atopic dermatitis (AD) is a chronic systemic disease with skin lesion, inflammation caused by mediators plays important role in its pathogenesis. Severe AD characterizes by permanent exacerbations that leads to sufferings and, influences on physical and emotional conditions and losses of patient's productivity. Modern drugs including biologicals have a good clinical efficacy, but the same time AD burden (cost of illness) in the Russian conditions are not evaluated yet. Direct medical and nonmedical costs, non-direct costs in severe AD in adults based on prevalence data, statistics of finances covering of out-patients and in-patients treatment options, experts' opinions, reports about temporary disability, losses of GDP etc. have been calculated. Burden of severe AD in local practice can be evaluated as 564 242 RUR/patient/year in working age and 263 230,5 RUR/patient/ year in aged population. Social-economic burden of severe AD in the Russian Federation can reach 13,074 Bln RUR annually (12,031 Bln RUR for working patients and 1,043 Bln RUR for aged population of patients). Direct non-medical and non-direct costs have at least 50 % of all expenditures that highlighting of social importance of severe AD.